Implementasi Pendidikan Karakter Dalam Pembelajaran Fiqih Santriwati Kelas 1 Smp Tahfidh Putri Al-Amien Prenduan - Afifah Tidjani; Tolak Ida (Publikasi Indonesia, 2022)
The rise of immoral cases among adolescents indicates a lack of character education. So that the world of education is expected to be a solution, especially in the world of Islamic boarding schools. One of them is through the learning of Islamic sciences such as Fiqh which is expected to be a